Dynamic clustering and re-dispersion in concentrated colloid-active gel composites. Issue 34 (19th August 2019) - Foffano, G.; Lintuvuori, J. S.; Stratford, K.; Cates, M. E.; Marenduzzo, D.
Abstract : We simulate the dynamics of concentrated colloidal suspensions in active gels. Activity can both aggregate particles or redisperse them. Abstract : We study the dynamics of quasi-two-dimensional concentrated suspensions of colloidal particles in active gels by computer simulations. Remarkably, we find that activity induces a dynamic clustering of colloids even in the absence of any preferential anchoring of the active nematic director at the particle surface. When such an anchoring is present, active stresses instead compete with elastic forces and re-disperse the aggregates observed in passive colloid-liquid crystal composites. Our quasi-two-dimensional "inverse" dispersions of passive particles in active fluids (as opposed to the more common "direct" suspensions of active particles in passive fluids) provide a promising route towards the self-assembly of new soft materials.